The Historical and Cultural Context of Liangzhu - Wang, Ningyuan. author. aut Link
XII, 112 p. 60 illus., 49 illus. in color.
Keywords: This book clarifies the advent of Liangzhu Culture and analyses the morphology, structure and internal social organization of grass-root settlements, medium-size settlements and the ancient city of Liangzhu, as well as the religious beliefs, ideology and power mechanisms represented by jade. Further, the book explains how the low-lying location and humid environment in the water-net plain area prompted the creation of man-made platforms or pillars, forming small and densely settled residential areas, and ultimately the water villages of southern China. Developments between man and nature accelerated the process of civilization, leading to the polarization of social classes and pyramid-shaped residential structures containing cities, towns and villages. Offering unique insights into the social vitality and structure of Liangzhu society, the book is one of the most important academic works on interpreting the origins of Liangzhu Civilization and investigating Chinese Civilization. .